2019
DOI: 10.26565/2313-6693-2019-37-08
|View full text |Cite
|
Sign up to set email alerts
|

Neurodynamic compensatory mechanisms of visual impairment and biomechanical indicators of running in an elite athlete in the paralympic sprint

Abstract: Introduction. The study of visual dysfunction compensatory mechanisms is of great importance both for the Paralympic athletes, as well as for people suffering from such dysfunctions, especially in cases when analyzer disorders occurred in adulthoodt, and natural adaptation mechanisms could not be included in the process of growth and development of the body. The aim: to identify potential compensatory mechanisms of visual impairment in an elite athlete in the Paralympic sprint based on an analysis of the biome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This helped her maintain a higher speed at a distance for a longer time compared with other athletes, which can be considered as a potential reserve [3,4,8]. There was also a slight unevenness in the change in speed and acceleration of the movement of the ankle and knee joints observed in some steps when lowering the limb after the hip was raised [17]. on the basis of a correlation analysis of neurodynamic and biomechanical characteristics, we pointed at an average and high significant relationship between the performance of the nervous system and running biomechanics [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This helped her maintain a higher speed at a distance for a longer time compared with other athletes, which can be considered as a potential reserve [3,4,8]. There was also a slight unevenness in the change in speed and acceleration of the movement of the ankle and knee joints observed in some steps when lowering the limb after the hip was raised [17]. on the basis of a correlation analysis of neurodynamic and biomechanical characteristics, we pointed at an average and high significant relationship between the performance of the nervous system and running biomechanics [17].…”
Section: Introductionmentioning
confidence: 99%
“…There was also a slight unevenness in the change in speed and acceleration of the movement of the ankle and knee joints observed in some steps when lowering the limb after the hip was raised [17]. on the basis of a correlation analysis of neurodynamic and biomechanical characteristics, we pointed at an average and high significant relationship between the performance of the nervous system and running biomechanics [17]. We concluded that the need to improve the biomechanics of running by focusing on the work of the kinaesthetic analyser could result in an increase in speed at a distance with its preservation almost to the finish line [17].…”
Section: Introductionmentioning
confidence: 99%